Analyzing Inner Conflict in “PRIDE.” Through Schema Theory and Metaphor - Lubis, Rafi Muhammad; Azahra, Naiya; Sinaga, Joyce Chardha; Siregar, Akbar Pangeran; Rangkuti, Rahmadsyah (Universitas Pahlawan Tuanku Tambusai, 2025)
Kendrick Lamar's 2017 song